Insertion of continuous real functions on spaces, bispaces, ordered spaces and point-free spaces - a common root - Ferreira, Maria João (2009)
We characterize normal and extremally disconnected biframes in terms of the insertion of a continuous real function in between given lower and upper semicontinuous real functions and show this to be the common root of several classical and new insertion results concerning topological spaces, bitopological spaces, ordered topological spaces and locales.